The impact of Roman army on trade and production in Lower Moesia (Moesia Inferior) - Duch, Michał (Studia Europaea Gnesnensia, 2015)
The paper presents the Roman army as the factor of change and economic transformation in the province of Lower Moesia. It addresses such issues as construction activities of the Roman army, development of the logistical base in order to meet the provisioning needs of the Roman troops. The main issue is the process of development of the local market of trade and production, as well as role of the Roman army in establishing and developing the fundamental branches of economy.